STRUKTUR REGULASI INDEPENDENSI OTORITAS JASA KEUANGAN - Bismar Nasution (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2014)
A non-independent regulatory structure in the financial services sector had already conduced poor economic condition for some countries in the 1990s. Learned from that experience, the existence of OJK in Indonesia must be supported by the existence of an independent regulatory structure so that the purpose of OJK being formed in the first place can be materialized. The existence of the independent regulatory structure, can be measured by OJK’s independence in terms of regulation, supervision, institutional, and independence in terms of financing. In the context of OJK in Indonesia, the independent regulatory structure, is not intended to make OJK as a catalyst for economic development or a referee for a fair play. OJK’s independence must be played to balance the interests of the government, consumer, and financial services industry so that the direction of economic policy can go hand in hand. Though not in the perfect shape yet, the regulation of OJK has already adopted all aspects from that independent regulatory structure. It was said not in the perfect shape yet, because a harmonization is still needed on a number of laws and regulations relating, and establishment of implementing regulations at the technical level of operational. With these, OJK is expected to be more objective and also can run its authority adequately, transparently, and accountably. Furthermore, OJK is expected to have a sufficient legal authority to conduct an investigation into the financial services issues. Keywords: Regulatory structure, independence, OJK